Syntagm and Intoneme: is the Equals Sign Possible? (in the Tradition of French Linguistics in Russia) - Olevskaia Mariia (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The author compares traditional and phonological methods of studying and describing intonation in French linguistics in Russia in connection with the notion of syntagm. The purpose of this comparison is to demonstrate benefits and shortcomings of both approaches to describing intonation and to find a solution to the question whether the notion of syntagm pertains to intonology or to syntax. The phonological method of describing intonation which has been developed by E. A. Bryzgunova in application to Russian and by M. M. Ruber in application to French material (and which is little familiar to many specialists dealing with French phonetics) allows us to resolve a range of contradictions and difficulties of the traditional approach, for example those connected with the use of the term syntagm. The author also traces the use of this term in French tradition with the aim of overcoming terminological confusion.